The regenerative role of adipose‐derived stem cells (ADSC) in plastic and reconstructive surgery - Naderi, Naghmeh (Blackwell Publishing Ltd, 2016)

(untitled) (Int Wound J)
The potential use of stem cell‐based therapies for the repair and regeneration of various tissues and organs offers a paradigm shift in plastic and reconstructive surgery. The use of either embryonic stem cells (ESC) or induced pluripotent stem cells (iPSC) in clinical situations is limited because of regulations and ethical considerations even though these cells are theoretically highly beneficial. Adult mesenchymal stem cells appear to be an ideal stem cell population for practical regenerative medicine. Among these cells, adipose‐derived stem cells (ADSC) have the potential to differentiate the mesenchymal, ectodermal and endodermal lineages and are easy to harvest. Additionally, adipose tissue yields a high number of ADSC per volume of tissue. Based on this background knowledge, the purpose of this review is to summarise and describe the proliferation and differentiation capacities of ADSC together with current preclinical data regarding the use of ADSC as regenerative tools in plastic and reconstructive surgery.